Carbene transfer: a new pathway for propargylic esters in gold catalysis - Lauterbach, Tobias; Gatzweiler, Sabrina; Nösel, Pascal; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2013)
Gold carbenes generated via 1,2-migration of a propargylic ester group can be transferred over a tethered alkyne. The use of aromatic backbones leads after a 1,7-carbene transfer to a benzyl-stabilized carbene as intermediate. A 1,2-shift of a methyl group delivers vinyl-substituted β-naphthol derivatives as the final products.